Work Method and SLA Performance in Procurement and Contract Operations: Evidence from Indonesia’s Upstream Oil and Gas Industry - Rida Elfreda Agustiana; Akbar Adhi Utama (Politeknik Siber Cerdika Internasional, 2026)
Background: Following organizational restructuring, Procurement and Contract Management (PCM) functions across Subholding entities in Indonesia’s upstream oil and gas sector show variation in Service Level Agreement (SLA) achievement linked to differences in work method, personnel allocation, and coordination practices; external factors such as regulatory requirements and digital system transformation may further shape these outcomes. Objective: This study analyzes SLA performance variation across Subholding entities and examines how work method, personnel allocation, and coordination influence procurement and contract management performance, extending operations-management literature on work specialization beyond single-sector confirmation toward context-specific evidence from a regulated, project-based industry. Methods: Using a convergent parallel mixed-method design (Creswell & Plano Clark, 2018), quantitative data from six Subholding entities (2024) were analyzed together with qualitative data from interviews and FGDs; the two strands were collected concurrently and merged during interpretation to provide complementary explanatory depth. Results: Split work methods achieved 45% faster SLA completion than end-to-end methods. Contract Assignment Ratio showed a weak negative but statistically insignificant correlation with SLA Compliance (Pearson r = -0.251, p = 0.631; n = 6), indicating limited statistical power from only six regional observations and suggesting that process coordination, execution quality, and capability differences, rather than personnel volume alone, more strongly explain SLA variation. Conclusion: Split work methods improve SLA performance through role specialization and coordination, while personnel allocation alone does not determine outcomes. Findings offer practical guidance for procurement governance, SLA monitoring, and capability development; generalization beyond a single industrial sector and a small regional sample remains limited.